An investigation into the variability of skin colour measurements. Issue 4 (10th April 2018) - Wang, Mengmeng; Xiao, Kaida; Luo, Ming Ronnier; Pointer, Michael; Cheung, Vien; Wuerger, Sophie
Abstract: This study aimed to investigate the variability of skin colour measurements for two kinds of extensively used instruments, telespectroradiometers (TSR) and spectrophotometers. A Konica Minolta CM700d spectrophotometer and a PhotoResearch PR650 telespectroradiometer were used to measure the forehead and the cheekbone of 11 subjects. The variability was evaluated using different measurement parameters including measurement aperture size and pressure on the facial locations for the spectrophotometer, and measurement distance for the telespectroradiometer. The mean colour difference from the mean was used to define the short‐term repeatability; the CIELAB colour difference and colour appearance changes in each perceptual CIELAB attribute between each of two instrument settings were used to evaluate the inter‐instrument agreement. The results show that, for the TSR, different measurement distances have identical repeatability but the colour shifts were significant; for the spectrophotometer, the large aperture size of the target masks gave the most repeatable results and the aperture size had more influence on the colour shifts than the measurement pressure. In addition, to investigate the effect of ethnicity and body location on measurement variability, skin colours from additional 151 subjects were measured. The differences between the measurements for different body locations were, in general, larger than the instrument repeatability and the inter‐instrument agreement.